Site impacts nutrient translocation efficiency in intraspecies and interspecies miscanthus hybrids on marginal lands. Issue 9 (22nd July 2022) - Magenau, Elena; Clifton‐Brown, John; Awty‐Carroll, Danny; Ashman, Chris; Ferrarini, Andrea; Kontek, Mislav; Martani, Enrico; Roderick, Kevin; Amaducci, Stefano; Davey, Chris; Jurišić, Vanja; Kam, Jason; et al.
Abstract: Miscanthus, a C4 perennial rhizomatous grass, is capable of growing in varied climates and soil types in Europe, including on marginal lands. It can produce high yields with low nutrient inputs when harvested after complete senescence. Senescence induction and rate depend on complex genetic, environmental, and management interactions. To explore these interactions, we analysed four miscanthus hybrids (two novel seed‐based hybrids, GRC 3 [ Miscanthus sinensis  ×  sinensis ] and GRC 14 [ M. sacchariflorus  ×  sinensis ]; GRC 15, a novel M. sacchariflorus  ×  sinensis clone; and GRC 9, a standard Miscanthus  ×  giganteus clone) in Italy, Croatia, Germany and the UK. Over all trial locations and hybrids, the average aboveground biomass of the 3‐year‐old stands in August 2020 was 15 t DM ha −1 with nutrient contents of 7.6 mg N g −1 and 14.6 mg K g −1 . As expected, delaying the harvest until spring reduced overall yield and nutrient contents (12 t DM ha −1, 3.3 mg N g −1, and 5.5 mg K g −1 ). At lower latitudes, the late‐ripening M. sacchariflorus × sinensis GRC 14 and GRC 15 combined high yields with low nutrient contents. At the most elevated latitude location (UK), the early‐ripening M. sinensis × sinensis combined high biomass yields with low nutrient offtakes. The clonal Miscanthus × giganteus with intermediate flowering and senescence attained similar low nutrient contents by spring harvest at all four locations. Seasonal changes in yield and nutrient levels analysed in this study provide: (1) a first step towards recommending hybrids for specific locations and end uses in Europe; (2) crucial data for determination of harvest time and practical steps in the valorization of biomass; and (3) key sustainability data for life cycle assessments. Identification of trade‐offs resulting from genetic  ×  environment  ×  management interactions is critical for increasing sustainable biomass supply from miscanthus grown on marginal lands. Abstract : Senescence induction and rate in miscanthus depend on complex genetic, environmental, and management interactions. To explore these interactions, this study compares seasonal aboveground yield, nutrient contents, and nutrient stocks of three novel miscanthus hybrids with a standard Miscanthus × giganteus clone at four European locations. The results provide a first step towards recommending hybrids for specific locations in Europe, crucial data for determination of harvest time, and key sustainability data for life cycle assessments. Identification of trade‐offs resulting from genetic  × environment  ×  management interactions is critical for increasing sustainable biomass supply from miscanthus grown on marginal lands.